2020
DOI: 10.1210/jendso/bvaa183
|View full text |Cite
|
Sign up to set email alerts
|

Severe Congenital Hypothyroidism Due to a Novel Deep Intronic Mutation in the TSH Receptor Gene Causing Intron Retention

Abstract: In three Somalian siblings with severe nongoitrous congenital hypothyroidism, exome sequencing identified a variant in TSHR predicted to be benign in isoform 3 but leading to an intronic mutation in isoform 1 (NM_00369:c.692 + 130C>A), which is the isoform expressed in the thyroid. This mutation creates a pseudo-exon that results in a protein that, if transcribed, would lack the transmembrane domain, thereby hampering its expression at the cell surface. Our findings illustrate that the interpretation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…One study, in a Saudi Arabian cohort, identified causative variants in 44% (11/25) of the cases with TD ( 40 ). However, in that study, when cases with TSHR variants, a gene associated with hypoplasia or apparent athyreosis but neither with ectopy nor with true athyreosis ( 41 , 42 ), were excluded, the discovery rate drops to 16%. Two other studies used targeted NGS to identify variants in CH-related genes in cases with CHTD ( 38 , 43 ).…”
Section: Discussionmentioning
confidence: 94%
“…One study, in a Saudi Arabian cohort, identified causative variants in 44% (11/25) of the cases with TD ( 40 ). However, in that study, when cases with TSHR variants, a gene associated with hypoplasia or apparent athyreosis but neither with ectopy nor with true athyreosis ( 41 , 42 ), were excluded, the discovery rate drops to 16%. Two other studies used targeted NGS to identify variants in CH-related genes in cases with CHTD ( 38 , 43 ).…”
Section: Discussionmentioning
confidence: 94%